PENINGKATAN PEMBENTUKAN KALUS JAMBU METE PADA KULTUR IN VITRO DARI EKSPLAN DAUN DAN MAHKOTA BUNGA - Ajijah, Nur; Yunita, Rossa (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The increasing of the callus formation of cashew (Anacardium occidentale L.) from leaf explants and the petals have successfully done through the use of a combination of plant growth regulators 2,4-D, pocloram and BA. On leaf explants the highest percentage of callus formation was obtained in combination treatment of plant growth regulators 2,4-D 5 mg/l + BA 1 mg/l and 2,4-D 5 mg/l + picloram 0.5 mg/l with callus formation percentage of 33.3%. On the use of petal explants the highest percentage of callus formation was obtained on 2,4-D treatment of 10 mg/l with callus formation percentage of 40%. Formed callus were blackish brown demonstrate the use of PVP 200 mg/l still can not overcome the problem of phenol oxidation.